2020
DOI: 10.1101/2020.12.25.20248860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Will Proton Pump Inhibitors Lead to a Higher Risk of COVID-19 Infection and Progression to Severe Disease? A Meta-analysis

Abstract: BackgroundPrevious researches on the association between proton pump inhibitors (PPIs) use and the treatment and prevention of COVID-19 have generated inconsistent findings. Therefore, this Meta-analysis was conducted to clarify the outcome in patients who take PPIs.MethodsWe carried out a systematic search to identify potential studies until November 2020. Heterogeneity was assessed using the I-squared statistic. Odds ratios (ORs) with its 95% confidence intervals (CIs) were calculated by fixed-effects or ran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We showed here that the previous use of PPIs is associated with increased risk of death from COVID-19. Such association is supported by a meta-analysis of eight studies ( 30 ) that showed that previous use of PPIs increases the risk of progression to severe COVID-19. Almario et al ( 31 ) recently described that individuals taking PPIs had greater chances for testing positive for COVID-19 when compared to those not using PPIs.…”
Section: Discussionmentioning
confidence: 86%
“…We showed here that the previous use of PPIs is associated with increased risk of death from COVID-19. Such association is supported by a meta-analysis of eight studies ( 30 ) that showed that previous use of PPIs increases the risk of progression to severe COVID-19. Almario et al ( 31 ) recently described that individuals taking PPIs had greater chances for testing positive for COVID-19 when compared to those not using PPIs.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, previous consumption of PPIs has been associated with an increased risk of COVID-19-related death, as demonstrated by Almario, Chey and Spiegel [ 118 ] . A meta-analysis of 8 studies [ 119 ] showing that prior PPI use raises the likelihood of COVID-19 development to a severe manifestation corroborated this association. In addition, PPI users had a greater likelihood of testing positive for COVID-19 than non-users Almario, Chey and Spiegel.…”
Section: Covid-19 and Lpr And Potential Aspirationmentioning
confidence: 87%
“…In the Cunye et al [56] analysis (online publication without a peer-review) of eight studies with more than 268,683 subjects, PPI use did not influence the risk of SARS-CoV-2 infection or mortality risk of COVID-19 patients, but the risk of severe disease (OR 1.54) and secondary infection (OR 4.33) was increased. However, the authors stress the need of more high-quality studies to further clarify the relationship.…”
Section: Impact Of Ppi Use In Covid-19 Pandemic -Evidence From the Re...mentioning
confidence: 97%